DIMENSI HUKUM PELANGGARAN KECELAKAAN LALU DAN ANGKUTAN JALAN LINTAS DI INDONESIA - Remincel Remincel (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Definition of traffic is the movement / move of human and animal vehicles on the road from one place to another by using a means of motion. The form of liability for traffic accidents that only results in material loss without life damages is in the form of compensation. Determine whether an accident resulting in material loss without loss of life is a crime or not, then the action is declared a criminal offense if it meets the elements of: a) Subject; b) Error; c) Is against the law (of action): An action that is prohibited or required by law / legislation and against violators is threatened with crime; d) Time, place and situation. If it is associated with a traffic accident as mentioned above, both minor, moderate and severe traffic accidents are crimes.